POSTHUMAN VOICE: EXAMINING THE NONHUMAN NARRATOR IN KAZUO ISHIGURO’S KLARA AND THE SUN - Kumar, Piyush; Jha, Arpana (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The portrayal of nonhuman characters in science fiction narratives underscores the intersection of fiction and posthuman subjectivity, expanding meaning-making beyond the human experience. These narratives challenge established humanist concepts and redefine our understanding of nonhuman modes of existence. Kazuo Ishiguro’s novel Klara and the Sun (2021) vividly exemplifies this posthuman theme by presenting a nonhuman character from a first-person perspective. The story unfolds through the eyes of Klara, an Artificial Friend designed to provide companionship to lonely teenagers. This study investigates how nonhuman elements contribute to the development of the literary text, considering the emerging role of the nonhuman as both character and narrator. It examines the interactions between a nonhuman narrator and human characters, emphasising the posthuman concept. The study focuses on the influence of nonhuman storytelling techniques and the significance of the artificial friend as a key narrative device. Additionally, it highlights how the author’s depiction of nonhuman agency shapes the narrative, leading to boundary crossings and a defamiliarisation of traditional storytelling that can evoke the uncanny valley effect. In Klara and the Sun, the anthropomorphised nonhuman narration signifies a paradigm shift that displaces humanity from its central role, affecting both the novel’s content and the reader’s experience.